Serum 25-hydroxyvitamin D concentrations in dogs with gallbladder mucocele - Jaffey, Jared A. (PLoS One, 2020)
Gallbladder mucocele (GBM) is a common biliary disorder in dogs. Gallbladder hypokinesia has been proposed to contribute to its formation and progression. The specific cause of gallbladder stasis in dogs with GBM as well as viable treatment options to resolve dysmotility remains unknown. Vitamin D deficiency is one of the many potential causes of gallbladder hypokinesia in humans and repletion results in complete resolution of stasis. Improving our understanding of the relationship between serum vitamin D and GBM could help identify dogs as a model for humans with gallbladder hypokinesia. Furthermore, this relationship could provide insight into the pathogenesis of GBM and support the need for future studies to investigate vitamin D as a novel treatment target. Therefore, goals of this study were i) to determine if serum 25-hydroxyvitamin(OH)D concentrations were decreased in dogs with GBM, ii) if serum 25(OH)D concentrations were different in clinical versus dogs subclinical for GBM, and iii) to determine if serum 25(OH)D concentrations could predict the ultrasonographic type of GBM. Sixty-two dogs (clinical, n = 26; subclinical, n = 36) with GBM and 20 healthy control dogs were included in this prospective observational study. Serum 25(OH)D concentrations were measured with a competitive chemiluminescence immunoassay. Overall, dogs with GBM had lower serum 25(OH)D concentrations than control dogs (P = 0.004). Subsequent subgroup analysis indicated that this difference was only significant in the subclinical group compared to the control dogs (P = 0.008), and serum 25(OH)D concentrations did not significantly differ between dogs clinical for GBM versus subclinical or control dogs, indicating that inflammatory state in clinical dogs was not the major constituent of the observed findings. Decreasing serum 25(OH)D concentrations, but not clinical status, was associated with a more advanced developmental stage of GBM type determined by ultrasonography. Our results indicate that vitamin D has a role in dogs with GBM. Additional studies are needed to assess if reduced vitamin D in dogs with GBM is a cause or effect of their biliary disease and to investigate if vitamin D supplementation could be beneficial for dogs with GBM.